Development and Initial Validation of a Web-Based Interactive Bilingual Module for MKDU Learning in Higher Education - Hendrik, Marion Derissilfia Grace; Yanti, Intan Ratna Sari; Muhammad, Muhammad; Pereira, Clarenca Sweetdiva; Neves, Joanino Gaspar Das; Kusumawardani, Heni (Reflection Journal, 2026)
Digital transformation in higher education requires adaptive, flexible, and relevant instructional materials that respond to the characteristics of digital-native students. General Basic Courses, locally referred to as Mata Kuliah Dasar Umum (MKDU), play a strategic role in developing interdisciplinary competencies; however, their instructional delivery remains largely conventional and has not been optimally integrated with digital technology and bilingual academic literacy support. This study aims to develop and conduct an initial validation of a web-based interactive bilingual module to support MKDU learning in higher education. This study employed a Research and Development (R&D) approach by adapting the Borg and Gall model, including needs analysis, product planning, initial prototype development, expert validation, product revision, and limited user testing. Data were collected through questionnaires administered to 30 students, semi-structured interviews with three MKDU lecturers, expert validation, and user response questionnaires involving 15 students. The needs analysis showed that 83.3% of students required web-based learning access, 86.7% needed bilingual presentation, and 90.0% preferred interactive quizzes and multimedia features. Expert validation indicated that the prototype was valid to highly valid, with Aiken’s V scores ranging from 0.88 to 0.91, while user responses showed good to very good ratings. The main contribution of this study is the development of an initial web-based bilingual MKDU module prototype that integrates user needs analysis, TPACK principles, bilingual academic terminology, multimedia, and formative quizzes within a unified digital learning environment.